EFEITO DA MASSA ESPECÍFICA NAS PROPRIEDADES DE FLEXÃO ESTÁTICA EM CONPENSADOS DE Pinus elliottii Engelm - Palma, Hernando Alfonso Lara [UNESP] (Universidade Federal de Santa Maria, 1999)
The objetive of this work was to determine the relation between the rigidity and strength properties in static bending and specific gravity of plywood manufactured from five veneers of Pinus elliottii Engelm from 30 year-old plantations. Linear simples, multiple and polynomial relations involving the modulus of rupture (MOR), modulus of elasticity (MOE), stress at proportional limit (TLP) and specific gravity (Me) of the plywood were studied. The specific gravity did not prove to be a very exact indicator of the rigidity and strength properties of the plywood. The MOE, MOR and TLP in static bending of the plywood showed low coefficients of correlations and determination adjusted for simple linear regression, indicating a little dependence of the specific gravity, the modulus of rupture in static bending on the principal directions (X and Y) had a strong dependence of the modulus of elasticity and stress at proportional limit. The coefficients of correlations of the best models of regression in the two directions varied from 0.85 to 0,91. The frequency histograms of the specific gravity of plywood showed a unimodal homogeneous distribution, while MOE and MOR showed a unimodal distribution with positive asymmetric skewness.

O presente trabalho teve por objetivo a determinação de relações entre as propriedades de resistência e rigidez à flexão estática e a massa especifica de painéis compensados de 5 lâminas feitos de madeira de Pinus elliottii Engelm, proveniente de plantios de 30 anos de idade. Foram estudadas várias relações lineares simples, múltiplas e polinomiais, envolvendo o módulo de ruptura (MOR), o módulo de elasticidade (MOE), a tensão no limite proporcional (TLP) e a massa específica (Me) dos compensados. A massa específica mostrou não ser indicador muito preciso das propriedades de resistência e rigidez dos painéis. As propriedades dos compensados à flexão estática, em termos de MOE, MOR e TLP mostraram baixos coeficientes de correlação e determinação ajustados por regressão linear simples, indicando pouca dependência de massa específica. O módulo de ruptura à flexão nas direções principais (x e Y), teve uma forte dependência do módulo de elasticidade e de tensão no limite proporcional. Os coeficientes de correlação dos melhores modelos de regressão nas duas direções variaram de 0,85 a 0,91, Histogramas de frequência da massa específica dos compensados mostraram uma distribuição unimodal homogênea, enquanto que o MOE e o MOR apresentaram uma distribuição unimodal com assimetria positiva.
EFECT OF THE SPECIFIC GRAVITY ON STATIC BENDING PROPERTIES IN PLYWOOD OF Pinus elliottii Engelm
Keywords: Plywoods; veneer; static bending in plywood; Pinus elliottii; Compensados; lâminas; flexão estática em compensados; Pinus elliottii